Vascular interventional strategies for recurrent nasopharyngeal carcinoma: diagnostic and therapeutic perspectives - Zhang, Qiang; Zhai, Xiang; Liu, Gang; Shang, Yanguo; Tong, Xiaoguang; An, Xingwei (Frontiers in Oncology, 2025)
ObjectiveThis study aimed to evaluate the role of vascular interventional techniques in the management of recurrent nasopharyngeal carcinoma as part of a multidisciplinary treatment framework.MethodsA retrospective analysis was conducted on the clinical records of 14 patients with recurrent nasopharyngeal carcinoma. All participants underwent digital subtraction angiography (DSA), balloon occlusion testing (BOT), and preoperative assessments to evaluate internal carotid artery (ICA) integrity, collateral circulation, and suitability for combined arterial infusion chemotherapy in the management of ICA bleeding. Postoperative evaluations included the assessment of distal blood perfusion following ICA embolization and subsequent ICA bypass procedures.ResultsDSA findings demonstrated compromised ICA involvement in three patients. Two patients with negative BOT results underwent coil embolization for hemostasis, whereas one patient with a positive BOT result received stent implantation to repair a pseudoaneurysm. This patient subsequently underwent an external carotid artery middle cerebral artery bypass, which restored satisfactory distal perfusion following ICA occlusion. Across all 14 patients, comprehensive treatment achieved substantial tumor regression with minimal systemic adverse effects. In addition, prompt intervention for ICA rupture and hemorrhage was effective, and no fatal complications occurred.ConclusionVascular interventional methods provided critical diagnostic and therapeutic value in the management of recurrent nasopharyngeal carcinoma. These approaches enabled the identification of tumor-feeding arteries, comprehensive assessment of vascular anatomy and distal perfusion, and mitigation of the risk of life-threatening hemorrhage. Their application established a secure foundation for subsequent therapeutic interventions targeting recurrent disease.